Characterization of Lactococcus lactis subsp. lactis isolated from surface waters - Svec, P; Sedlácek, I (Folia microbiologica, 2008)
A group of nine presumptive enterococci was isolated on enterococcal selective media Slanetz-Bartley agar and/or kanamycin-esculin-azide agar during a screening of Enterococcus spp. in surface waters. All strains formed a homogeneous cluster separated from all enterococcal species using rep-PCR fingerprinting with the (GTG)5 primer but they matched fingerprints revealed by Lactococcus lactis subsp. lactis representatives. Further identification using extensive biotyping and automated ribotyping with EcoRI (RiboPrinter microbial characterization system) confirmed all strains as L. lactis subsp. lactis in full correspondence with the (GTG)5-PCR. We demonstrated that L. lactis subsp. lactis strains occur in different surface waters and can be confused with enterococci due to their positive growth on selective enterococcal media as well as positive results in tests commonly used for identification of the genus Enterococcus (esculin hydrolysis, acetoin and pyrrolidonyl arylamidase production, growth at 10 degrees C and in 6.5% NaCl). The (GTG)5-PCR fingerprinting was revealed as a reliable and fast method for the identification of L. lactis subsp lactis while automated ribotyping with EcoRI proved to be a good tool for intrasubspecies typing purposes.
Keywords: Polymerase Chain Reaction; sladká voda; Bacterial Typing Techniques; DNA Fingerprinting; Fresh Water; Phylogeny; Lactococcus lactis; fylogeneze; techniky typizace bakterií; DNA fingerprinting; polymerázová řetězová reakce